Physiological performance and serum Na+, K+ Ca2 + and Mg2 + regulation of black tiger prawn (Penaeus monodon Fabricius 1798) reared in varying Na+/K+ ratios of inland saline water - Tantulo, U.; Fotedar, Ravi (Elsevier BV, 2017)
A 28-day trial was conducted to investigate the serum ionic regulation of juvenile black tiger prawns (Penaeus monodon Fabricius 1798) of 1.2 ± 0.1 g mean initial weight, reared in varying Na+/K+ ratios of inland saline water (ISW). The serum Na+, K+, Ca2 + and Mg2 + regulation, osmoregulatory capacity (OC), isosmotic points, survival, growth and condition indices of P. monodon were measured when P. monodon were reared in four different ISW types having Na+ and K+ ratios of 119.4 (represented by raw ISW control having higher Na+/K+ ratio), 6.5, 12,0 and 16.2. The first water type of ISW (control) was at 5 ppt (ISW5) and the other 3 were at the salinities of 5 ppt (ISWK5), 10 ppt (ISWK10) and 15 ppt (ISWK15) which were fortified with K+ equivalent to [K+] in the ocean water of 25 ppt. P. monodon juveniles reared in ISW5 and ISWK15 regulated their serum Na+ and K+ stronger than juveniles reared in ISWK5 and ISWK10 and brought the serum Na+/K+ ratios closer to the normal Na+/K+ ratio of OW. Serum Ca2 + and Mg2 + of the juveniles reared in ISWK10, were regulated strongly over the trial period. However, the juveniles reared in ISW5 and ISWK15 had increased serum Ca2 + at day 28. After 14 days of rearing, the serum osmolality of juveniles decreased significantly from 640.2 and 649.6 mOsm to 550.1 and 562.2 mOsm in ISWK5 and ISWK10 respectively. In contrast, the serum osmolality and OC of juveniles reared in ISW5 (control) remained constant over the 14 day period but then increased significantly toward the end of the trial. During the initial 14 days of rearing, 20.8 and 20.5% of the juveniles survived in ISWK5 and ISWK10 respectively. However, 100% of juveniles died at the end of the trial. In contrast, the juveniles reared in ISW5 and ISWK15 were able to survive until the end of the trial with a survival rate of 37.5 and 62%, respectively. At the end of the trial, the SGR and condition indices of juveniles reared at ISW5 and ISWK15 showed no significant difference (P < 0.05). At day 14, the amount of food ingested by the juveniles reared in ISWK5 and ISWK10 were significantly lower than the juveniles reared in ISW5 and ISWK15. The exoskeleton moisture content (EM %) and dry exoskeleton index (Ebd) of juveniles reared in ISW5 were significantly higher and lower respectively, than the EM % and Ebd of juveniles reared in ISWK15. This trial suggested that P. monodon juveniles faced unfavourable medium Na+ and K+ ratio in ISW through strong regulation of [Na+] and [K+] which enabled the prawns to establish normal ratios of Na+ and K+ in their haemolymph ranging from 21.42 to 25.97 mg/L which were similar to the normal haemolymph ratio of Na+ and K+ of prawns reared in OW ranging from 22.3 to 29.9.